1990
DOI: 10.1113/jphysiol.1990.sp017998
|View full text |Cite
|
Sign up to set email alerts
|

Nerve‐mediated contractions of sheep mesenteric lymph node capsules.

Abstract: SUMMARY1. Isometric tension was recorded in vitro from strips cut from the capsules of mesenteric lymph nodes of sheep.2. One minute periods of field stimulation at frequencies of 1, 2, 4, 8 and 16 Hz (pulse duration, 0 3 ms) elicited tonic contractions of increasing force and duration. The stimulus frequency-response relationship began to flatten out at frequencies > 4 Hz, where the response was already 72 % of that at 16 Hz.3. The response to field stimulation was abolished by tetrodotoxin (1 ,UM).4. Phentol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
1

Year Published

1990
1990
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 16 publications
1
10
1
Order By: Relevance
“…A new stable tension level was attained within 60-90 sec. In high-potassium solution with norepinephrine, LN CS tension rapidly increased at a rate typical of spontaneous phase contractions [12] and reached a new steady level over 45-60 sec.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…A new stable tension level was attained within 60-90 sec. In high-potassium solution with norepinephrine, LN CS tension rapidly increased at a rate typical of spontaneous phase contractions [12] and reached a new steady level over 45-60 sec.…”
Section: Resultsmentioning
confidence: 97%
“…Then, the length of the strip was increased step by step (with 0.5 mm intervals) and the tension was recorded. When stable tension was reached, physiological saline in the chamber was replaced with a solution where Na + was replaced with K + +10 5 M of norepinephrine hydrochloride (Sigma) [7,12]. When a new stable CS tension level was attained, physiological saline was added to the chamber.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphedema under such circumstances is thought to be due to the development of inflammation and possible fibrosis of the superficial lymph vessels as complications of synovitis, with subsequent obstruction of lymphatic flow due to lymph node swelling, etc. 2,4,5,12,13 However, it has been reported that some of the patients did not show any correlation between severity of lymphatic impairment and duration or severity of arthritis, 4,5 suggesting that local factors other than lymphatic function may influence the threshold below which edema occurs. Casley-Smith and Piller have reported that lymphedema was partially derived from the failure of macrophages to absorb protein in the tissue fluid.…”
Section: Discussionmentioning
confidence: 95%
“…The contractile activity is regulated by a complex interplay between biomechanical forces and electrical activity; the latter generated from pacemaker potentials termed spontaneous transient depolarizations [28,29,30]. It is also of interest to note that the lymph nodes themselves have contractile potential and might contribute to lymph propulsion [31, 32]. The loss of water in the nodes with the resulting concentration of lymph-borne proteins has been postulated to allow greater amounts of protein to be returned to the bloodstream within the finite pumping limits of the lymphatic system [22].…”
Section: Discussionmentioning
confidence: 99%